1982
DOI: 10.1128/aac.22.4.711
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of new beta-lactam antibiotics and other antimicrobial drugs against anaerobic isolates from obstetric and gynecological infections

Abstract: The in vitro activities of N-formimidoyl thienamycin, clindamycin, chloramphenicol, metronidazole, cefoperazone, cefotaxime, cefoxitin, moxalactam, penicillin G, and piperacillin were determined against 158 anaerobic bacteria isolated from endometrial wash cultures of women with pelvic infections. In general, Nformimidoyl thienamycin was the most active, with all organisms inhibited by cO.5 jig/ml. Chloramphenicol, clindamycin, and metronidazole inhibited all organisms by c8 ,ug/ml. The penicillins and cephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
3
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…Knowledge of this distribution allows a logical choice of antimicrobial agents adequate for the therapy of infections in these sites. Following the recent description of B. disiens and B. bivius, they were recognized as important bacteroides isolated in OBG infections (15,20). AGPC were the second most frequently recovered anaerobes and accounted for 26% of anaerobic isolates, a finding similar to reports in previous studies (2, 14, 17, 18, 22).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Knowledge of this distribution allows a logical choice of antimicrobial agents adequate for the therapy of infections in these sites. Following the recent description of B. disiens and B. bivius, they were recognized as important bacteroides isolated in OBG infections (15,20). AGPC were the second most frequently recovered anaerobes and accounted for 26% of anaerobic isolates, a finding similar to reports in previous studies (2, 14, 17, 18, 22).…”
supporting
confidence: 82%
“…Bacteroides are important anaerobic pathogens that can be recovered from a variety of infections (7,14). Members of the B. fragilis group are primarily isolated from abdominal infections (5), pigmenting Bacteroides group members are isolated from oral and respiratory tract infections (6), and B. disiens and B. bivius are isolated from female genital tract infections (15,20).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the susceptibility pattern of our isolates were similar to that reported by other groups (1,10,11,18,21). In this study the most active agent in vitro was ceftizoxime, followed by a 2:1 combination of amoxicillin and clavulanic acid.…”
supporting
confidence: 75%
“…Penicillin G, on the other hand, demonstrated relatively poor activity overall against genital strains of Bacteroides spp., not only just the B. fragilis group, expressing substantial activity only against fusobacteria and gram-positive species. Similar results for some of the same species and antimicrobial agents which were obtained from endometrial wash specimens have been reported (16).…”
supporting
confidence: 72%
“…Of a total of 22 strains of P. anaerobius, the MIC of moxalactam was .8 ,ug/ml for nine strains, whereas the other strains had moxalactam MIC values of <2 ,ugIml. Three strains for which the MIC of moxalactam was -64 ,ug/ml were, in addition, considerably less susceptible than the other strains to cefotaxime (MICs, 4 ,ug/ml) and to cefoperazone, cefoxitin, and penicillin G (MICs, 8 to 16 ,ug/ml or U/ml). A similar VOL.…”
mentioning
confidence: 99%